The impact of creativity in developing a new product according to customer requirements, an analytical study in Al-Mansour General Company - سعدون محسن سلمان (Iraqi Journal for Administrative Sciences, 2025)
Impact of creativity in the development of a new product according to customer’s requirements: Analytical study in the Al Mansour General Company Play compete in the global market an important role and critical t and impose many challenges, requiring them to respond to these challenges through the adoption of mechanisms renewed in line with the requirements of dealing with the developments in the state of competition existinfacing companies in their quest to survive and stay in the markeg in the market today. The development of a new product is necessary for the survival and growth of the company, part of the strategic objective, and presents the development of a new product to the returns of large companies that can do properly. Is very expensive also if its a sinner and can lead to the failure of whole job, and on this basis is an innovation in the development of a new product, taking into account the requirements and the needs and desires of the customer based mainly in the strengthening of the company towards success and progress in the field of competition and ensuring excellence and leadership. In this context, addressing the current search to the problem of research have implications for academic and field in terms of the ability of the company’s research sample on the face of competition in the domestic market in pursuit of establishing itself as a springboard to regional and global markets, has Tacher main objective of the research in an attempt to prove the impact of innovation and the development of a new product to achieve customer needs and requirements, in order to achieve this was launched research hypotheses two major, linked to the first extent of a correlation between creativity and develop new product according to customer requirements, and determine the second and the presence of the impact of creativity in the development of a new product according to customer’s requirements, has been a set of conclusions and proposals related to research problem and achieved its objectives.